S‐velocity characterization of the crust and upper mantle structure beneath the Bay of Bengal. (16th January 2018) - Corchete, V.
Abstract : A 3D S‐velocity model has been determined from fundamental‐mode Rayleigh‐wave analysis in a wide period band (from 5 s to 175 s), to attain the characterization of the geologic structures existing in the Bay of Bengal, from 0 to 300 km depth. This model is presented by means of S‐velocity maps. In these maps, the S‐velocity in the depth range from 0 to 10 km is principally affected by the distribution of the sediment deposits. The S‐velocity generally increases with depth, showing the lowest values for shallow depths in which are present unconsolidated sediments. The S‐velocity mapping also allows the clear differentiation between the 85E Ridge and the 90E Ridge. The lower S‐velocity determined for the 85E Ridge compared with its adjacent region suggests that this ridge is less dense than its adjacent region. The existence of compensation beneath both ridges also is definitively confirmed in the Moho map performed in this study. The lower S‐velocities determined for the regions of the Andaman Sea and the northernmost part of the Bay of Bengal, in the depth range from 15 to 40 km, are associated to the existence of a thick crust beneath this regions. The results obtained in the present study confirm that the crust beneath the Bay of Bengal is in general thin crust. Although the controversy about the nature of the crust beneath the Bay of Bengal (is it oceanic or continental?) still persist, the results of the present study show that both hypotheses (oceanic crust and continental crust) are reasonable. The 3D S‐velocity model shows that the huge sediment load located at the northernmost part of the Bay of Bengal has originated at the thickening of the crust and the lithosphere, whereas the asthenosphere is almost unaffected by this load. This model also shows that the subduction of the Indian Plate below the Burma Plate, at the east of the Sunda Trench, also has produced a thickening of the crust and the lithosphere, but the asthenosphere is almost not affected by this effect. Finally, the dependency of the S‐velocity with the age of the lithosphere and the asthenosphere is shown very clearly for the lithosphere whereas it is only slight visible for the asthenosphere.